Development of a database for the rapid and accurate routine identification of Achromobacter species by matrix-assisted laser desorption/ionization–time-of-flight mass spectrometry (MALDI-TOF MS). (January 2021) - Garrigos, T.; Neuwirth, C.; Chapuis, A.; Bador, J.; Amoureux, L.; ,; Andre, E.; Barbier, E.; Caillon, J.; Cardot-Martin, E.; Cattoir, V.; Doléans-Jordheim, A.; et al.
Abstract: Objectives: Achromobacter spp. are emerging pathogens in respiratory samples from cystic fibrosis patients. The current reference methods ( nrdA- sequencing or multilocus sequence typing) can identify 18 species which are often misidentified by conventional techniques as A. xylosoxidans . A few studies have suggested that matrix-assisted laser desorption/ionization–time-of-flight mass spectrometry (MALDI-TOF/MS) provides accurate identification of the genus but not of species. The aims of this study were (a) to generate a database for MALDI-TOF/MS Bruker including the 18 species, (b) to evaluate the suitability of the database for routine laboratory identification, and (c) to compare its performance with that of the currently available Bruker default database. Methods: A total of 205 isolates belonging to the 18 species identified by nrdA sequencing were used to build a local database. Main spectra profiles (MSPs) were created according to Bruker's recommendations for each isolate with the Biotyper software. Performance of the default Bruker database and ours for routine use were compared by testing 167 strains (including 38 isolates used from MSP creation) belonging to the 18 species identified by nrdA sequencing directly from colonies cultivated on various media. Results: Our new database accurately identified 99.4% (166/167) of the isolates from the 18 species (score ≥2.0) versus only 50.9% (85/167) with the Bruker database. In the Bruker database 17.3% of the isolates (29/167) were incorrectly identified as another species despite a score of ≥2.0. Conclusions: The use of MALDI-TOF/MS in combination with a database developed with samples from 18 Achromobacter species provides rapid and accurate identification. This tool could be used to help future clinical studies. Graphical abstract: Image 1